Psychic Suffering: Identified Influences on the Process of Professional Choice in Young People - Figueiredo, Samara Leite de (2023)
The general objective of the research is to identify the determining phenomena that involve the process of professional choice, considering the suffering generated by the act of deciding on a future career in young people in a pre-university preparatory course. The methodology used was a questionnaire with objective and subjective questions, the data were analyzed from the quantitative and qualitative approach, using representations of charts and graphs, emphasizing descriptive statistical analysis and Bardin's content analysis. The results obtained corresponded to the presentation of factors that influence the professional choice that cause psychic suffering in young people, they indicated that concerns arise reflecting insecurities, nervousness and anxieties, highlighting the entry into the job market, family expectations, media and professional status, expectations regarding the future project refers to personal value, quality of life and personal and professional recognition. It is considered that it is of great relevance the adoption of scientific productions and interventions aimed at the field of professional guidance, which can ease the psychic suffering on the occasion of the professional choice, avoiding dissatisfaction and dropping out of school.